14.4: Polychromatic High‐Frequency Steady‐State Visual Evoked Potentials for Brain‐Display Interaction. Issue 1 (1st July 2013) - Chien, Yu‐Yi; Lin, Fang‐Cheng; Chou, Ching‐Chi; Zao, John K.; Kuo, Heng‐Yuan; Huang, Yi‐Pai; Wang, Yijun; Jung, Tzyy‐Ping; Shieh, Han‐Ping D.
Abstract An oncoming interactive platform integrated with LCD provides another option not only for handicapped but public to make our daily lives more convenient. Steady‐state visual evoked potentials (SSVEPs) are human brain responses to visual stimulation at specific light flashing frequencies. With the improvement of brain‐computer interface (BCI) applications in mind, this paper proposed effective and comfortable SSVEP stimuli of high‐frequency and polychromatic encoded lights with tunable duty cycles and phases.